Assessment of Groundwater in Al-Hawija (Kirkuk Governorate) for Irrigation Purposes. - Awadh, Salih; Al-Kilabi, Joudah (Iraqi Journal of Science, 2023)
The study area is located in Kirkuk governorate - northern Iraq, It covers an area of 630 km2.Twenty eight groundwater samples were collected from the study area during October 2012. pH, electrical conductivity(EC) and total dissolved solids (TDS) and chemical analysis of major ions (Ca2+, Mg2+, Na+, K+, Cl, SO42 and HCO3) were determined. Sodium adsorption ratio (SAR), residual sodium carbonate (RSC), sodium percent (Na%) and electrical conductivity were used to evaluate the suitability of groundwater for irrigation purpose. The groundwater samples mostly have no harmful effects and no hazard in terms of SAR and RSC respectively, and permissible in terms ofNa%, but they are poor, very poor and marginal as irrigation water.